Experiences of Climate Change Adaptation in Africa - Leal Filho, Walter (Climate Change Management, 2011)
It is widely acknowledged that, in addition to global and regional efforts to cope with climate change by means of mitigation measures, adaptation initiatives can and perhaps should play a key role in enabling communities from across Africa to better handle the problems related to it. Due to the fact that experiences in climate change adaptation in Africa are poorly documented, this book provides an attempt to address the perceived need for better documentation and dissemination of African experiences on climate change adaptation.